Perbedaan Perubahan Intensitas Disminorea antara Kompres Hangat dan Kompres Dingin pada Siswi Kelas VII dan VIII SMP - trevia, reni; Eka Seba Marta; Milya Novera; Mimi Rosiska; Ikhrimni (Jurnal Amanah Kesehatan, 2025)
In Indonesia, 107,673 people (64.25%), consisting of 59,671 people (54.89%) had primary dysmenorrhea and 9,496 people (9.36%) had secondary dysmenorrhea. The impact of dysmenorrhea on adolescents is that it can interfere with learning activities and daily activities. The aim of the study was to determine the difference in the intensity of dysmenorrhea between warm compresses and cold compresses for female students at Baiturrahmah Padang Middle School.This type of research uses quantitative, namely Quasi-experimentalwith a one group pretest posttest design.. The sampling technique was purposive sampling. The sample size is 18 respondents and the data obtained was processed using univariate, bivariate and multivariate methods. The results of the Manova test multivariate variables with a significant level of α < 0.05 indicate that the f test has a significance value of 0.000 < α 0.05. It can be seen that the f tests are all significant. The significance value of the Levene test shows that both variables on the pre-test dysmenorrhea scale have a value of f = 6,790 with a significance of 0.005 <0.05. Meanwhile, on the dysmenorrhea post test scale, the value off =5,237 with a significance of 0.013<0.05. Then whatisseenis the Games- Howell test. From the post hoc test, it can be seen the difference between warm compresses and cold compresses, warm compresses are 1.22, while cold compresses are 0.89. the conclusion of the study, there was a significant difference by giving warm compresses and cold compresses to reducing the intensity of dysmenorrhea in Baiturrahmah Padang Middle School students that warm compresses were more effective in reducing dysmenorrhea than cold compresses. Keywords: Disminorea; Warm Compresses; Cold Compresses